Communication between natural killer T cells and adipocytes in obesity. (1st October 2016) - Satoh, Masashi; Iwabuchi, Kazuya
ABSTRACT: Adipose tissue contains various types of immunocompetent cells, and these cells of innate and adaptive immunity control adipose tissue inflammation that blunts insulin sensitivity. Recent studies have shown that adipocytes express CD1d and present lipid antigen(s) to activate natural killer T (NKT) cells. The function of adipocytes is in turn modulated by cytokines that NKT cells produce to alter the expression of anti-inflammatory adipokine(s) and the production of inflammatory and chemoattractant cytokines. These in vitro studies imply that the interaction between adipocytes and NKT cells might affect the development of not only obesity but also obesity-related diseases. To test the importance of the interaction between NKT cells and adipocytes, we examined whether an adipocyte-specific CD1d deletion affected the development of obesity, which had been demonstrated with B6.CD1d −/− (CD1d KO). We found that the interaction is indeed important to induce adipose tissue inflammation and insulin resistance in response to lipid excess. In this commentary, the advances and controversies on NKT cells and obesity are discussed based on our recent report that NKT cells play a pivotal role in the regulation of adipose tissue by communicating with adipocytes via CD1d.